Acute posterior multifocal placoid pigment epitheliopathy with cerebral involvement. Issue 1 (January 1991) - Stoll, G; Reiners, K; Schwartz, A; Kaup, F G; Althaus, C; Freund, H J
Abstract : In a patient with angiographically proven cerebral vasculitis five months after acute posterior multifocal placoid pigment epitheliopathy (APMPPE) neurological symptoms promptly responded to steroid treatment. Cerebrospinal fluid (CSF) showed a lymphocytic pleocytosis. Magnetic resonance imaging (MRI) revealed multifocal white matter lesions in the hemispheres and the brain stem suggesting a diffuse subcortical vasculitis.